PENGARUH LEVERAGE DAN FINANCIAL DISTRESS TERHADAP KONSERVATISME AKUNTANSI - Munajat, Muhammad Arish (2015)
Penelitianinibertujuanuntukmengujisecaraempiristerkaitdengan (1) pengaruhleverageterhadapkonservatismeakuntansidan (2) pengaruhtingkatfinancial distressterhadapkonservatismeakuntansi.Penelitianinidilakukandikarenakanditemukannyabeberapafenomenaterkaitkondisikeuanganperusahaan yang diukurmenggunakantingkathutangdanjuganilaiakrualperusahaan.Dimanadalammengukurtingkatkonservatismeakuntansimenggunakan model Non-Operating Accrual. Penelitianinimenggunakansampelperusahaangrupbakrie yang listing di Bursa Efek Indonesia (BEI) periode 2009 - 2013 denganmenggunakan sampling jenuhsehinggaterkumpul 7 perusahaansebagai sample penelitian.Penelitianinimenggunakanmetodeasosiatifkausaldenganteknikanalisis data regresi data panel. Hasilpenelitianmenunjukanbahwakedua variable independenmempengaruhiterhadap variable dependendansebagaipenghubungnyamenggunakanteoriakuntansipositif. DimanahasilnyatingkatLeverage tidakadapengaruhpositifterhadapkonservatismeakuntansidikarenakannilaikoefisiendalamregresibernilai negative. Sehingga H0diterimadan Ha ditolak.Sedangkanfinancial distresstidakadapengaruh negativeterhadapkonservatismeakuntansi yang ditandaipadakoefisienregresibernilaipositifsehingga H0 diterimadan Ha ditolak.Sehinggauntukkedua variable tidakmendukungadanyateoriakuntansipositif. Kata Kunci: Leverage, Financial Distress,dan Konservatisme Akuntansi This study aims to test empirically related to (1) the effect of leverage to accounting conservatism and (2) the effect of the level of financial distress to accounting conservatism. This study was conducted due to the discovery of several related phenomena company's financial condition as measured using the level of debt and the accrual of the company. Where in measuring the level of accounting conservatism using Non-Operating Accrual models. This study used a sample of Bakrie group companies listed on the Indonesian Stock Exchange (BEI) in the period from 2009 to 2013 by using a sampling saturated and collected 7 companies as research samples. This study uses the causal associative data analysis techniques panel data regression. The results showed that both independent variables influence the dependent variable and as the connecting using positive accounting theory. Leverage levels where the results is not positive effect on accounting conservatism due to the regression coefficient negative worth. So H0 is accepted and Ha is rejected. While the financial distress is not a negative effect on accounting conservatism that marked the regression coefficient is positive so that H0 is accepted and Ha rejected. So for the two variables does not support the existence of positive accounting theory. Keyword: Leverage, Financial Distress, and Accounting Conservatism